Systemic Diseases in Patients with Congenital Aniridia: A Report from the Homburg Registry for Congenital Aniridia - Jessica Obst; Fabian N. Fries; Maryam Amini; Annamária Náray; Cristian Munteanu; Tanja Stachon; Shweta Suiwal; Neil Lagali; Berthold Seitz; Barbara Käsmann-Kellner; Nóra Szentmáry (Ophthalmology and Therapy)
Abstract Introduction Congenital aniridia is increasingly recognized as part of a complex syndrome with numerous ocular developmental anomalies and non-ocular systemic manifestations. This requires comprehensive care and treatment of affected patients. Our purpose was to analyze systemic diseases in patients with congenital aniridia within the Homburg Aniridia Registry. Methods Our retrospective, monocentric study included patients who underwent a comprehensive ophthalmic examination at Saarland University Medical Center beginning in June 2003. Age, gender, genetic test results, and information on systemic anomalies were recorded. In addition, parents and affected patients were interviewed about developmental and other disease-related conditions. Results Data from 337 patients (mean age 22 ± 20 [0.3–90] years; 181 women [53.7%]) were analyzed. Genetic testing was performed in 187 (55.5%) patients. A PAX6 mutation was detected in 174 of 187 (93%) cases, of which 20 (10.7%) had WAGR(O) syndrome. Systemic diseases were detected in 155 of 337 (46%) patients, with the most common being obesity (29 [8.6%]), thyroid disease (28 [8.3%]), hypertension (26 [7.7%]), intellectual disability (22 [6.5%]), diabetes mellitus (19 [5.6%]), auditory perception disorder/speech development delay (16 [4.7%]), and epilepsy (12 [3.6%]). Conclusions A comprehensive analysis of patients with aniridia and systemic effects reveals the complexity of this rare disorder, which goes beyond ocular symptoms and can have profound effects on metabolic balance, cardiovascular health, and the central nervous system. Therefore, early genetic diagnosis, early systemic checkup, and adequate treatment, as well as cooperation with pediatrists, neurologists, and audiologists, is suggested in congenital aniridia, which should be considered a syndrome and not an isolated ocular disease.